Putative DNA-dependent RNA polymerase in Mitochondrial Plasmid of Paramecium caudatum Stock GT704 - Trina Ekawati Tallei (Bogor Agricultural University, Indonesia, 2015)
Mitochondria of Paramecium caudatum stock GT704 has a set of four kinds of linear plasmids with sizes of 8.2, 4.1, 2.8 and 1.4 kb. The plasmids of 8.2 and 2.8 kb exist as dimers consisting of 4.1- and 1.4-kb monomers, respectively. The plasmid 2.8 kb, designated as pGT704-2.8, contains an open reading frame encodes for putative DNA-dependent RNA polymerase (RNAP). This study reveals that this RNAP belongs to superfamily of DNA/RNA polymerase and family of T7/T3 single chain RNA polymerase and those of mitochondrial plasmid of fungi belonging to Basidiomycota and Ascomycota. It is suggested that RNAP of pGT704-2.8 can perform transcription without transcription factor as promoter recognition. Given that only two motifs were found, it could not be ascertained whether this RNAP has a full function independently or integrated with mtDNA in carrying out its function.